Illegal Construction as a Criminal Offense in the Republic of North Macedonia: Legal Analysis - Veseli Shkëlqim; Arifi Besa (SEEU Review, 2025)
Illegal construction, as defined by the Criminal Code of the Republic of North Macedonia, is classified as a criminal offense under the chapter on Criminal Offenses against Property. Every municipality in North Macedonia faces challenges related to illegal construction. These constructions cause significant financial, urban, and environmental harm— impacting not only the state and municipal budgets but also citizens indirectly.